2018
DOI: 10.1074/jbc.ra118.001812
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sequences orchestrate subcellular trafficking of neuronal PAS domain–containing protein 4 (NPAS4)

Abstract: Neuronal Per-Arnt-Sim (PAS) domain–containing protein 4 (NPAS4) is a basic helix–loop–helix (bHLH)-PAS transcription factor first discovered in neurons in the neuronal layer of the mammalian hippocampus and later discovered in pancreatic β-cells. NPAS4 has been proposed as a therapeutic target not only for depression and neurodegenerative diseases associated with synaptic dysfunction but also for type 2 diabetes and pancreas transplantation. The ability of bHLH-PAS proteins to fulfil their function depends on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 62 publications
(85 reference statements)
1
16
0
Order By: Relevance
“…In silico analysis suggested the presence of NLSs in the bHLH domain, the PAS-2 domain and the C-terminal region of NPAS4. Accordingly, putative NESs were expected to be located in the bHLH domain, the PAS-2 domain and the C-terminal region of NPAS4 [21]. For the purpose of this review, we have repeated all predictions (Table 1, Supplementary Materials 1, Supplementary Materials Summary), which are generally still consistent.…”
Section: Regulation Of the Subcellular Localization Of Class I Bhlmentioning
confidence: 88%
See 3 more Smart Citations
“…In silico analysis suggested the presence of NLSs in the bHLH domain, the PAS-2 domain and the C-terminal region of NPAS4. Accordingly, putative NESs were expected to be located in the bHLH domain, the PAS-2 domain and the C-terminal region of NPAS4 [21]. For the purpose of this review, we have repeated all predictions (Table 1, Supplementary Materials 1, Supplementary Materials Summary), which are generally still consistent.…”
Section: Regulation Of the Subcellular Localization Of Class I Bhlmentioning
confidence: 88%
“…We performed detailed in vivo experiments, which revealed the presence of two overlapping signals: NLS (10-52aa) and NES (26-45aa) in bHLH domain. Simultaneously in the region adjacent to PAS-2 domain and within this domain in close proximity are located: NLS (158-191aa), NES (227-242aa) and putative NLS (285-316aa) [21]. We demonstrated that C-terminal region of NPAS4 contains overlapping NES (591-600aa) and putative NLS (593-622aa).…”
Section: Regulation Of the Subcellular Localization Of Class I Bhlmentioning
confidence: 99%
See 2 more Smart Citations
“…For SIM2 C-terminal region cytoplasmic localization was documented [111]. Finally, we demonstrated previously the presence of overlapping NES and NLS in the C-terminal region of NPAS4 [112]. PTMs like phosphorylation, especially close to the NLS/NES were shown to regulate the intracellular distribution of proteins via activation/deactivation of the localization motifs [113].…”
Section: Discussionmentioning
confidence: 51%